PENGARUH BODY DISSATISFACTION DAN SELF-ESTEEM DENGAN PERILAKU DIET MAHASISWI UNIVERSITAS â€œXâ€ SERTA TINJAUAN DALAM ISLAM - Rahmania Hanum; Entin Nurhayati; Siti Nur Riani (Lembaga Penelitian Universitas YARSI, 2014)
Abstract. Diet is an effort to reduce or control the consumption of foods which aims to reduce or maintain body weight (Hawks, 2008). The initial survey showed 17 of the 30 students of the Faculty of Psychology YARSI on a diet and reduce the frequency of eating to get the more ideal body. This study aims to look at the effect of body dissatisfaction and self-esteem with dietary behaviors among girls. This research is expected to be useful and help young women to seek information on a healthy diet behavior and its relation to body dissatisfaction, and self-esteem. This study used 100 participants (students of â€œXâ€ University) were determined by simple random sampling method. Measurements using 28 items of dietary behavior attitude scale, 34 items of BSQ scale and self-esteem scale adaptation of Heatherthon Polivy consists of 20 items. The results of this study using multiple regression analysis showed that: that body dissatisfaction and self-esteem affect dietary behavior University student